Desain Iot Untuk Smart Kumbung Dengan Thinkspeak Dan Nodemcu - Wajiran Wajiran; Sampurna Dadi Riskiono; Purwono Prasetyawan; Muhammad Iqbal (P3M Politeknik Negeri Banjarmasin, 2020)
Mushroom Kumbung is a house to take care of mushroom baglog and grow mushrooms, made from bamboo or wood. This Kumbung must have the ability to maintain the temperature and humidity of the mushroom so that it grows optimally. Control of the condition of mushroom kumbung is usually done manually, by spraying water on the mushroom baglog. This is less effective when a farmer has many kumbung, especially if far from his home. This requires a technology that can control and monitor the temperature and humidity of the kumbung. This research designs Internet of Things (IoT) technology for smart kumbung systems to condition their temperature and humidity. This research method is experimental with a quantitative approach. This study tried Thingspeak as an IoT platform with NodeMCU as its microcontroller. The sensor used for sensing humidity and temperature is DHT22 with an actuator is a sprayer, a blower and a lamp. Realtime temperature and humidity monitoring data can be accessed through an internet browser. The system works functionally according to the desired work design. Error value from the reading of the DHT22 sensor with a Digital Thermometer Hygrometer measuring instrument is still in the working area of DHT22.